Notes and Comments. (Catholic Historical Review)
The article announces that Katrina B. Olds received the 2016 John Gilmary Shea Prize, Andrew Berns received the 2016 Howard R. Marraro Book Prize, and San Francisco State University professor William Issel received the American Catholic Historical Association (ACHA) 2017 Distinguished Scholar Award.